2019
DOI: 10.1016/j.jsat.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of medication assisted treatment for opioid use in prison and jail settings: A meta-analysis and systematic review

Abstract: This study examined the state of the literature on the effectiveness of medication assisted treatment (MAT; methadone, buprenorphine, naltrexone) delivered in prisons and jails on community substance use treatment engagement, opioid use, recidivism, and health risk behaviors following release from incarceration. Randomized controlled trials (RCTs) and quasi-experimental studies published through December 2017 that examined induction to or maintenance on methadone (n=18 studies), buprenorphine (n=3 studies), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(117 citation statements)
references
References 66 publications
2
109
1
5
Order By: Relevance
“…A recent meta-analysis examining the effectiveness of MAT delivered in prisons and jails found promising results with methadone treatment (Moore et al, 2019). There were not enough studies of buprenorphine or naltrexone to meta-analyze, but data from trials in which methadone was provided during incarceration demonstrated increased community treatment engagement and reduction in illicit opioid and injection drug use (Moore et al, 2019). In a randomized control trial of individuals recently released from prison, XR-NTX plus counseling showed improved relapse outcomes compared to counseling or treatment referrals alone (Lee et al, 2016).…”
Section: Medication Assisted Treatment (Mat) In Justice Settingsmentioning
confidence: 99%
“…A recent meta-analysis examining the effectiveness of MAT delivered in prisons and jails found promising results with methadone treatment (Moore et al, 2019). There were not enough studies of buprenorphine or naltrexone to meta-analyze, but data from trials in which methadone was provided during incarceration demonstrated increased community treatment engagement and reduction in illicit opioid and injection drug use (Moore et al, 2019). In a randomized control trial of individuals recently released from prison, XR-NTX plus counseling showed improved relapse outcomes compared to counseling or treatment referrals alone (Lee et al, 2016).…”
Section: Medication Assisted Treatment (Mat) In Justice Settingsmentioning
confidence: 99%
“…1,2 Treatment with methadone or buprenorphine can mitigate adverse consequences and decrease mortality. [3][4][5][6][7] Despite the strong evidence and clinical guidelines supporting use of these medications, [8][9][10] as many as 80% of patients do not receive such potentially life-saving treatments. 7,11 To address this treatment gap, the emergency department (ED) has emerged as an important location to identify patients with OUD and initiate buprenorphine with referral for ongoing treatment.…”
Section: Introductionmentioning
confidence: 99%
“…While jail-and prison-based treatment programs in the US are slowly shifting to align their services with evidence-based approaches (30)(31)(32), the uptake of MAT in prison and jail systems has been limited (33,34). In addition, the research supporting MAT in corrections settings is largely focused on prison-based or integrated jail-prison systems rather than on jail-based programs (35). In the Choices program, clients are now eligible to receive a long-acting opioid antagonist, naltrexone (brand name Vivitrol).…”
Section: Discussionmentioning
confidence: 99%